Giant Cell Tumor of Bone: Review of Current Literature, Evaluation, and Treatment Options - Montgomery, Corey; Couch, Cory; Emory, Cynthia L.; Nicholas, Richard (The Journal of Knee Surgery, 2019)
Giant cell tumor of bone is a benign albeit aggressive tumor commonly affecting the bones of the knee. Patients with these tumors present with pain, swelling, and inability to bear weight on the involved extremity. These destructive tumors typically arise in the metaphyseal region of the long bones in individuals in the second, third, and fourth generations of life. Histologically, the multinucleated giant cells are the hallmark of the lesion, easily recognized on histological review, which recently have become therapeutic targets for medical management of the disease. For decades, surgical management has been the primary treatment for giant cell tumor of the bone. Some tumors can be treated with excision and filling of the osseous void with bone cement or allograft. This is an effective treatment option with a low to moderate risk of local recurrence while preserving limb function. For more destructive tumors, wide excision and reconstruction with prosthetic, structural allograft or combined allograft prosthetic components are utilized. Advances in medical management of the disease have also demonstrated promise as an effective treatment; however, its use has usually been limited to the treatment of metastatic disease, recurrent disease or when advanced local disease would require surgical treatment felt to be overly morbid.
Keywords: giant cell tumor of bone; distal femur; proximal tibia; knee; denosumab